Re-description of the type series of Nectophrynoides viviparus (Bufonidae), with a taxonomic reassessment - Loader, Simon P.; Poynton, John C.; Davenport, Tim R. B.; Rödel, Mark-Oliver (Zootaxa, 2009)
The type series of Nectophrynoides viviparus (Tornier, 1905) from the southern Tanzanian highlands has been rediscovered in the Museum für Naturkunde, Berlin. A re-description is given and a lectotype designated. Available topotypic material is included in our assessment of morphological variation in this population. With clarification of the species’ identity, nomenclatural confusions can be addressed. We reject the designation of an earlier neotype, and also of records attributed to the species north and east of the Southern Highlands.